Vegetable Market Chain Analysis in Mecha District, West Gojjam Zone, Amhara National Regional State - , Aemro Worku Ayalew (Archives of Current Research International, 2018)
The study attempts to investigate the marketing channels of vegetables, to identify the actor who gets the major share of the marketing margins in vegetable marketing channels at the study area and to discover the major factors of market supply of vegetable in Mecha District. Descriptive and causal explanatory research design was employed with an aim of describing the market chain map of vegetables and stating the determinants of market supply of vegetables in Mecha District. The study was done at Department of Marketing Management, Aksum University between February 2018 and May 2018. The study included 120 farmers and 20 traders that involve in vegetable production and marketing activities. Producers, brokers, cooperatives, local collectors, wholesalers, retailers and consumers were found the main actors of the marketing channel in the study area. Six major channels for onion and five major channels for tomato were identified based on volume of the commodities transacted in the channels. Retailers were identified as the parties who take the largest Net Marketing Margin both in onion and tomato market channels. Retailers take 30.3 percent of the final consumer price in the onion market as Net Marketing Margin and they take 54.16 percent of the final consumer price in tomato market. The factors which determine market supply of onion were identified as education level of the household head, access to market, access to market information and price. For tomato, the factors which determine its market supply were identified as education level of the household, experience and price. The study mainly concludes that producers were not getting their deserving marketing margins while the intermediaries’ are taking advantage from them. Therefore the producers are in need of marketing support that may decrease the number of intermediaries and ensure them a larger marketing margin out of their produces.